IMPACT OF PANDEMIC PERIOD OF COVID-19 ON ONLINE LEARNING AND TEACHING IN TEACHER EDUCATION - Sundararasan, T.; Kalaiyarasan, ‪G. (Revista Prâksis, 2022)
Online learning is an educational process which takes place over the Internet as a form of distance education. Distance education became ubiquitous as a result of the Covid-19 pandemic. Because of these circumstances, online learning and teaching had an indispensable role in teacher education programs, even though debates continue on whether or not it is beneficial for prospective teachers to be exposed extensively to Information and Communication Technology (ICT). This descriptive study demonstrates how a student teacher course in teacher education was redesigned to provide student teachers with opportunities to learn and practice through online. It reports experiences and reflections from a practicum course offered in the teacher education courses in the Tirunelveli. It describes three phases of the online student teachers’ experiences Preparation, Implementation, and Reflection. Tasks accomplished in each phase are reported. Online teaching experiences provided these student teachers with opportunities to interact with others, as well as to encourage reflection on how best to promote prospective teachers development and learning with online communication tools.